First‐in‐class pyrido[2, 3‐d]pyrimidine‐2, 4(1H, 3H)‐diones against leishmaniasis and tuberculosis: Rationale, in vitro, ex vivo studies and mechanistic insights. Issue 4 (1st February 2022) - Ramesh, Deepthi; Sarkar, Deblina; Joji, Annu; Singh, Monica; Mohanty, Amaresh K.; G. Vijayakumar, Balaji; Chatterjee, Mitali; Sriram, Dharmarajan; Muthuvel, Suresh K.; Kannan, Tharanikkarasu
Abstract: Pyrido[2, 3‐ d ]pyrimidine‐2, 4(1 H, 3 H )‐diones were synthesized, for the first time, from indole chalcones and 6‐aminouracil, and their ability to inhibit leishmaniasis and tuberculosis (Tb) infections was evaluated. The in vitro antileishmanial activity against promastigotes of Leishmania donovani revealed exceptional activities of compounds 3, 12 and 13, with IC50 values ranging from 10.23 ± 1.50 to 15.58 ± 1.67 µg/ml, which is better than the IC50 value of the standard drug pentostam of 500 μg/ml. The selectivity of the compounds towards Leishmania parasites was evaluated via ex vivo studies in Swiss albino mice. The efficiency of these compounds against Tb infection was then evaluated using the in vitro anti‐Tb microplate Alamar Blue assay. Five compounds, 3, 7, 8, 9 and 12, showed MIC100 values against the Mycobacterium tuberculosis H37 Rv strain at 25 µg/ml, and compound 20 yielded an MIC100 value of 50 µg/ml. Molecular modelling of these compounds highlighted interactions with binding sites of dihydrofolate reductase, pteridine reductase and thymidylate kinase, thus establishing the rationale of their pharmacological activity against both pathogens, which is consistent with the in vitro results. From the above results, it is clear that compounds 3 and 12 are promising lead candidates for Leishmania and Mycobacterium infections and may be promising for coinfections. Abstract : Novel pyrido[2, 3‐ d ]pyrimidine‐2, 4(1 H, 3 H )‐diones were synthesized to fight leishmaniasis and tuberculosis infections. Compounds 3, 12 and 13 inhibited Leishmania donovani promastigotes, with IC50 values ranging from 10.23 ± 1.50 to 15.58 ± 1.67 µg/ml. Compounds 3 and 12 yielded MIC100 values of 25 µg/ml against Mycobacterium tuberculosis . Compounds 3 and 12 are thus promising lead candidates for Leishmania and Mycobacterium infections.